PENERAPAN PRINSIP MUZARA’AH DALAM MENINGKATKAN PENDAPATAN PETANI JAGUNG DI KABUPATEN PINRANG SULAWESI SELATAN - Hermiati, Hermiati; Pasigai, Aris (Universitas Muhammadiyah Makassar, 2019)
The purpose of this study was to determine the application of the principle of Muza>ra’ah in increasing the income of farmers in Bakaru Village and to determine the understanding of corn farmers about the muzara'ah principle in Bakaru Village. The type of research method used is descriptive qualitative in which using field research methods (primary data) and library research (secondary data). Primary data is data taken from the first source in the field in this study, namely the owners of rice fields and smallholder farmers, while secondary data is obtained from literature studies by reading books that are related to the title raised by the author. The results showed that the form of agricultural land sharing in Bakaru Village between landowners and smallholder farmers was adjusted to the agreement of the two parties, such as one-third, one-third and one-quarter by looking at who provided the seeds and operational costs and looking at natural conditions if crop failure.